Dismantling Fabricated Reality in Shepard’s State of Shock - Ziyad Shakir Loaybi Al-Zayadi; Asst. Prof. Thamir R. S. Az-Zubaidy (Ph.D.) (Journal of College of Education, 2023)
ABSTRACT This paper investigates Sam Shepard’s States of Shock in which the playwright explores family relation during an international crisis, war. As male identity is noted as a recurring theme in Shepard’s plays, the paper examines masculine identity in States of Shock. As depicted in the play, Colonel and Stubbs, the main characters in the play, struggle to negotiate their personal identity prisms. As such, we explore this issue via the lens of social identity to address the primary constructs in the play. Although taking as its setting a family café, the events in the play transcend this both temporally and spatially through the two characters’ battle for male identity at the war front lines. As such, we argue that through the characters of Colonel and Stubbs, where the former promotes war mythologies regardless of the suffering of the traumatized soldier, Stubbs, the play presents a critique of American myths of war.